Предмет: Математика,
автор: sofiya542
Упростить выражение (раскрыть скобки).
1) (3х+у) –2 (5х – у) = 3х+у – 10х+2у = –7х+3у;
2) 3х(а+1,5) –4ах = 3ах+4,5х – 4ах = 4,5х – ах;
3) –6 (х + у)+3 (2х – у) = – 6х – 6у + 6х – 3у = –9у.
nktselepov:
всё сделано жн
Ответы
Автор ответа:
1
Ответ:
3х+у-10х+2у=3х+у-10х+2у=-7х+3у
3ха+4.5-4ах=3ах+4.5х-4ах=4.5х-ах
-6х-6у+6х-3у=-6х-6у+6х-3у=-9у
Похожие вопросы
Предмет: Русский язык,
автор: Незнайка543
Предмет: Другие предметы,
автор: stas200000
Предмет: Русский язык,
автор: cveta2005
Предмет: Математика,
автор: инна1382
Предмет: Алгебра,
автор: keklol2289